Storm runoff pollution from a residential catchment in Miri, Sarawak - Ho, Carrie; Choo, B.Q. (University Putra Malaysia Press, 2014)
In this paper, stormwater runoff from a residential catchment located in Miri, Sarawak, was characterized to determine the pollutant concentrations and loading. The observed average event mean concentrations were 116 mg/L for TSS, 115 mg/L for COD, 1.5 mg/L for NH3-N, and 0.23 mg/L for Pb. Based on Interim National Water Quality Standards (INWQS) for Malaysia, the average event mean concentration, EMC value for TSS exceeded class II (50 mg/L), exceeded class V (>100 mg/L) for COD, and exceeded class III (0.9 mg/L) for NH3-N. All four water quality parameters exhibited first flush characteristic but to varying magnitude which was influenced by the storm characteristics.